PERAN PERAWAT DALAM MEMBERIKAN DUKUNGAN SPIRITUAL PADA LANJUT USIA DI PANTI SOSIAL TRESNA WERDHA YOGYAKARTA UNIT ABIYOSO - Asti Yulianti Atapada; Titih Huriah; Aris Budi Pratama (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2015)
ABSTRACT  Background: Spiritual need is a need to find out the meaning and objective of life, to forgive and to be forgiven. Nurses have assist the elderly facing spiritual distress and improve health or spiritual strength of the elderly through spiritual welfare.  Objective: To know role of nurses in providing spiritual support to the elderly at Tresna Werdha Social Institution of Abiyoso Unit Yogyakarta Method: The study was descriptive analitik used to get an accurate overview of all characteristics observed. Samples consisted of 56 people taken through quota sampling technique. Data were obtained through questionnaire and analyzed using univariate method.  Result: Role of nurses as care provider to the elderly was in good category (78.6%), as advocacy provider was in average category (44.6%), as educator was in average category (55.4%), as coordinator was in good category (44.6%), as collaborator was in good category (57.1%), as consultant was in good category (44.6%), as change of agent was in good category  (55.4%). Conclusion: Role of nurses in a good category are as care provider, coordinator, collaborator, consultant and change  agent. Role of nurses in average category are as advocacy and educator.  Suggestion: Nurses at Tresna Werdha Social Institution of Abiyoso Unit Yogyakarta were supposed to pay attention to efforts that could improve spiritual support to the elderly.